Deep Learning Approaches for English-Marathi Code-Switched Detection - Bhimanwar, Shreyash; Viralekar, Onkar; Anturkar, Koustubh; Kulkarni, Ashwini (EAI Endorsed Transactions on Scalable Information Systems, 2023)
During a conversation, speakers in multilingual societies frequently switch between two or more spoken languages. A linguistic action known as "code-switching" particularly alters or merges two or more languages. The development of software or tools for detecting code-switching has received very little attention. This paper proposes a Deep Learning based methods for detecting code-switched English-Marathi data. These suggested methods can be applied to various applications, including phone call merging, Intelligent AI assistants, Intelligent travelling systems to assist travellers in navigation and reservations, call centres to handle customer service issues, etc. To create a system for code switch detection, our study demonstrates a detailed analysis of extracting several audio features such as the Mel-Spectrogram, Mel-frequency Cepstral Coefficient (MFCC), and Perceptual Linear Predictive coefficients (PLP). Our team’s English-Marathi code-switched dataset served as the testing ground for our methodologies. Our model’s accuracy was 92.99%, with 40 MFCC coefficients having energy coefficient serving as the zeroth coefficient.